Application occupational safety and health in industry case study : CCM Fertilizers Sdn Bhd - Idris, Md Yusof (2008)
In today’s world, rapid economic development has not only led to significant improvements in incomes and the quality of life, but also resulted in great increases in the number of people killed and injured at work. For decades, industries have embraced many systems to minimise workplace accidents and incidents, yet despite the best intention, there has been little reduction in the rate at which people are killed or injured at work. Similar scenario prevails in Malaysia, when statistics from the Social Security Organisation reports indicated that although the number of occupational accidents has reduced gradually, workers especially those in the manufacturing sector still suffer a high level of occupational accidents almost every year. To overcome this problem, the government has come out with a legislative framework to deal with this situation. This study therefore has the purpose of examining safety related matters at work, strictly from the legal point of view. Its objectives are to investigate and analyze the existing system of Occupational Safety and Health in selected industries and to promote and OSHA act 1994 and to improve the safety and health at the selected industry. Qualitative method prone to the legal style of doing research was employed to achieve all the objectives. Hence the data referred in this study consist of all secondary data found in the legislations, journals of safety measurement, thesis and publications of safety measurement. It was found in this study that the selected industry almost obey the regulation of Occupational Safety and Health Act 1994. The results also showed that an accident in the workplace can be controlled if the employers obey the rule of OSH.